Pengaruh Buku Modul Praktik Clinical Skill Terhadap Kemampuan Mahasiswa Keperawatan Dalam Melakukan Pemeriksaan Fisik Dada - Fajar Agung Nugroho; Dadi Santoso; Wuri Utami (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2020)
Background: the competencies that must be possessed by a nursing student when they practice on the clinics or hospital, they must be able to carry out about physical examinations, determine nursing diagnoses, plan, implement, and evaluate nursing actions.Purpose: to know the effect of the clinical skills practice module on the nursing studentâ€™s ability in a chest physical examinationMethod: this research used True Experimental in the form of Posttest Only Control Design. Using two groups selected randomly into the control and treatment group. Where the control group will be given a conventional method and treatment group will be given a clinical skill module that is made by researchers.Result: t value was -6,625 < t table (1,658), so that it can be concluded that there is different between the treatment group and control group. Recommendation: Nursing process always interest to be discussed, hopefully the next research can explore about nurseâ€™s physical assessment ability in anotherÂ Keywords:Clinical skill module, nurse assessment, lungs physical assessment